Implementasi Algoritma RLE Untuk Kompresi Gambar Produk Pada Sistem Penjualan di Toko Dede Frozen Food Berbasis Web - yati nurhayati; Sherly Gina Supratman (TI S1 FKOM UNIKU, 2023)
According to the Ministry of Cooperatives and SMEs of the Republic of Indonesia (2017), out of the total number of business actors in Indonesia, Micro, Small, and Medium Enterprises (MSMEs) hold a very high market share (99.99%), with one of the sectors being trade. One MSME in Ciawigebang District, Kuningan Regency, operating in the trade sector is Dede Frozen Food Store. Based on the data collected, the problems faced by new MSMEs include the absence of a digital-based sales system, forcing them to purchase ready-made applications at high costs, along with periodic upgrade fees. Additionally, the lack of an image compression feature in these applications leads to high memory usage, making network access inefficient and time-consuming. These issues hinder the development of MSMEs, especially small businesses, due to the high capital required for application usage. Therefore, a study is needed to assist MSMEs in managing digital sales systems without requiring frequent upgrades and with the capability to compress images—particularly product images—to improve data processing and access speed. The research method used for system development is the Prototype method, which consists of three stages: user needs analysis (using interview techniques, observation, and literature study), design and implementation (UML, the RLE algorithm for image compression using PHP and MySQL programming languages), and testing (black-box, white-box, and User Acceptance Testing). The result of this research is an application that can be implemented by MSMEs in the trade sector, particularly for the research object, to handle image compression and sales system management.